Using electromagnetic methods to map and delineate high-grade harzburgite pods within the Ni-Cu mineralised Jacomynspan ultramafic sill, Northen Cape, South Africa - Ushendibaba, Mhaka (My University, 2016)
The Jacomynspan Ni-Cu sulphide mineralisation is hosted within a 100m thick steeply dipping tabular, differentiated, sill of mafic to ultramafic composition intruded into country gneissic rocks of the Namaqualand Metamorphic complex. This sill is predominantly composed of tremolite schist (metamorphosed pyroxenite) containing lenticular bodies of harzburgite. The harzburgite generally hosts net-textured mineralisation with up to 50% by volume of the rock. Massive sulphide veins and stringers are occasionally present within the harzburgite. The sulphide minerals are a typical magmatic assemblage of pyrrhotite, chalcopyrite and pentlandite. The sill covers an approximate strike length of about 5km but only a small portion covering 1km x 1km was selected for this study. Physical property studies carried out on the drill core (magnetic susceptibility and conductivity) indicate that the country gneissic rocks are not conductive and neither are they magnetically susceptible. However, the mineralized sill has elevated values of both magnetic susceptibility and relative conductivity compared to its host making it a suitable target for both magnetic and electromagnetic inversion. Drilling done so far on the study area has shown that the well-mineralised harzburgite (hosted within the poorly mineralised ultramafic sill) is not a continuous body but occurs in ‘pockets’. There is therefore need to use the available geophysical and geological datasets to derive a model of these well mineralised pods. This study is therefore intended to assess the feasibility of using electromagnetic (EM) methods together with other geophysical methods and geology in obtaining a model of the harzburgite pods hosted within the less conductive poorly mineralised ultramafic sill in order to guide further drilling. Geosoft’s VOXI Earth Modelling software was used to model the high resolution airborne magnetic data for this study. Cooper’s Mag2dc (www.wits.ac.za) and Stettler’s Magmodintrp software (personal communication, 2015) was also used during modelling of the magnetic data to compliment the modelling from VOXI. The mineralised ultramafic sill was clearly mapped in both the 3D model representation from Mag2dc modelling and VOXI’s 3D unconstrained smooth model inversion for the study area. Based on the physical properties studies carried out on the study area, EM data (both ground and downhole EM) were modelled using Maxwell software. The poorly mineralised tremolite schist was clearly modelled. In order to better constrain the targets, an assumption was made that at late decay times the currents would be focused in the centre of the large EM plate probably giving an indication of the most conductive part of the intrusion. Smaller ‘Resultant EM plates’ of dimensions, 300mx300m that coincide with the centre of the large EM plates (with a conductance above 100S) were constructed in iv Maxwell software and integrated with the DXF file of the Micromine geology model of the well mineralised harzburgite clearly mapping the well-mineralised harzburgite and showing its possible extensions. 2D inversion modelling was conducted on all audio-frequency magnetotelluric (AMT) data for this study area. The modelling results clearly mapped the mineralised intrusion.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2016.
Keywords: Metamorphic rocks--South Africa--Namaqualand; Geology, Structural--South Africa--Namaqualand; Geochemistry--South Africa--Namaqualand; Prospecting--Geophysical methods--Mathematical models